Psychology of the Subject’s Self-Regulatory Activity in the Context of Hybrid Warfare - Makarchuk, Nataliia; Kulinenko, Liliia; Vasylieva, Olga; Zhurkova, Olga; Makarchuk, Liudmila; Mozoliuk, Elena (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Objective: The main tasks of this study are as follows: to substantiate the interdependence of perversion as a form of violence and the human ego in the context of hybrid warfare; to prove the existence of perversion as a form of violence against a person in the context of hybrid warfare in Ukraine (personal perversion); to describe the alteration of ego states as conditions for effective human self-regulatory activity in the context of hybrid warfare. Background: Hybrid warfare, including the Ukrainian-Russian conflict, as a phenomenon, has been widely studied both abroad and in Ukraine. However, there are very few works on the psychological impact of such a war. There are currently no works on disorders of human self-regulatory activity in the context of hybrid warfare, which makes the study unique and relevant. Method: The study used a combination of various methods, in particular, structural-clinical interviews, psychological counseling and therapeutic meetings, data analysis. Data were collected for 2014-2020. The total number of participants was 55 people aged 25 to 63 years, with 70% female and 30% male. Results: The latent tension and denial of hybrid warfare result in a gradual increase of neurotization, which is in 95% of cases passes into a neurosis state with concomitant manifestations of symptoms. There is also a deterioration in psychological well-being and phylogenetic disorders (erogenous dysfunction in men, uncontrolled neurotic masturbation in women). Disorders of the mental level of self-regulation determine the manifestation of the mental content of perversion, in which perversion takes on the character of intrapersonal functioning. Conclusion: The combination of disorders of the physical, mental and personal levels of the self-regulatory activity of the psyche increased perverse tendencies in social and political life, which provoked a high rate of psychotization of the entire society and an increase in deficit characterological manifestations of each individual.